2006
DOI: 10.1074/jbc.m608727200
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Functional Conservation of the DNA Non-homologous End-joining Protein, XLF/Cernunnos

Abstract: Non-homologous end-joining is a major pathway of DNA double-strand break repair in mammalian cells, deficiency in which confers radiosensitivity and immune deficiency at the whole organism level. A core protein complex comprising the Ku70/80 heterodimer together with a complex between DNA ligase IV and XRCC4 is conserved throughout eukaryotes and assembles at double-strand breaks to mediate ligation of broken DNA ends. In Saccharomyces cerevisiae an additional NHEJ protein, Nej1p, physically interacts with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
105
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 59 publications
4
105
0
Order By: Relevance
“…Cernunnos orthologues (referenced as Nej1p or XLF1) have further been found in many eukaryotes demonstrating that Nej1p and Cernunnos/XLF belong to the same protein family (Callebaut et al, 2006;Hentges et al, 2006;Cavero et al, 2007). Nej1p in yeast interacts with the XRCC4 orthologue Lif1p, suggesting that Nej1p and Cernunnos/XLF have conserved an analogous function throughout evolution.…”
Section: Cernunnosmentioning
confidence: 99%
See 4 more Smart Citations
“…Cernunnos orthologues (referenced as Nej1p or XLF1) have further been found in many eukaryotes demonstrating that Nej1p and Cernunnos/XLF belong to the same protein family (Callebaut et al, 2006;Hentges et al, 2006;Cavero et al, 2007). Nej1p in yeast interacts with the XRCC4 orthologue Lif1p, suggesting that Nej1p and Cernunnos/XLF have conserved an analogous function throughout evolution.…”
Section: Cernunnosmentioning
confidence: 99%
“…Cernunnos is ubiquitously expressed and localized predominantly in the nucleus. Sequence analysis revealed that Cernunnos shares structural features with XRCC4 revealing the existence of a new protein family (Callebaut et al, 2002;Ahnesorg et al, 2006;Hentges et al, 2006). Based on the XRCC4 structure (Junop et al, 2000;Sibanda et al, 2001), one can predict a similar conformation for Cernunnos, that is a globular head domain followed by a coil-coiled tail Callebaut et al, 2006;Hentges et al, 2006).…”
Section: Cernunnosmentioning
confidence: 99%
See 3 more Smart Citations